2016
DOI: 10.1039/c5cy01195g
|View full text |Cite
|
Sign up to set email alerts
|

A smart catalyst system for the valorization of renewable furfural in aliphatic alcohols

Abstract: A highly efficient and selective oxidative condensation–hydrogenation process of renewable furfural with aliphatic alcohols mediated by supported Pt catalysts in a one-pot reactor is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Up to now, several examples dealing with the oxidation of 2-FA in the presence of heterogeneous catalysts have been reported [23][24][25][27][28][29]. These papers mainly deal with the use of gold supported catalysts [25,[27][28][29] demonstrating the current efforts to modify furfural-based derivatives by gold catalysis, due to the fact that such supported metal systems are mainly used as suitable catalysts for selective oxidation.…”
Section: Furfural Oxidative Esterification To Methyl-2-furoatementioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, several examples dealing with the oxidation of 2-FA in the presence of heterogeneous catalysts have been reported [23][24][25][27][28][29]. These papers mainly deal with the use of gold supported catalysts [25,[27][28][29] demonstrating the current efforts to modify furfural-based derivatives by gold catalysis, due to the fact that such supported metal systems are mainly used as suitable catalysts for selective oxidation.…”
Section: Furfural Oxidative Esterification To Methyl-2-furoatementioning
confidence: 99%
“…Nevertheless, a highly efficient and selective one-pot process involving the oxidative condensation and the hydrogenation of furfural with aliphatic alcohols catalyzed by metallic platinum has been reported very recently [23]. The authors examined several typical supported Pt catalysts and bases as catalysts for the reaction and found high conversion and selectivity when working in the presence of 5% Pt/HT (HT = hydrotalcite Mg/Al ratio equal to 3) and of potassium carbonate either in the furfural-ethanol-O 2 system, or in the furfural-n-propanol-O 2 one.…”
Section: Furfural Oxidative Esterification To Methyl-2-furoatementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the catalytic conversion pathways extend to ethanol oxidation condensation, which could provide an important breakthrough for diversication and sustainable development of hydrocarbon biofuel production. [14][15][16] Oxide-supported gold nanoparticles have emerged as a promising heterogeneous catalyst in the aerobic oxidation of alcohols. [17][18][19] For example, Haruta et al reported the N-formylation of amines via the aerobic oxidation of methanol over supported gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal NPs were studied for application in "smart" catalysts with switchable, tunable and reusable catalytic properties. 9,[16][17][18][19][20][21][22][23] To be successfully applied, metal NPs should be not only dispersed but also sensitive to external stimulus. 9,[16][17][18][19][20][21][22][23] Functionalization of metal NPs with stimuliresponsive polymers represents one of the choices to satisfy such requirements.…”
Section: Introductionmentioning
confidence: 99%